Integrating RNA-Seq and linkage mapping to identify and characterize qESCT2, a cold tolerance QTL at the early seedling stage in rice - Liu, Wenqiang; Chen, Zuwu; Guo, Liang; Dong, Zheng; Yang, Biaoren; Liu, Licheng; Liu, Sanxiong; Pan, Xiaowu (Frontiers in Plant Science, 2025)
Cold stress significantly limits rice productivity, particularly at the early seedling stage. Identifying key genes responsible for cold tolerance is crucial for breeding resilient rice varieties. In the study, we identified a quantitative trait locus (QTL), qESCT2, associated with cold tolerance at the early seedling stage. The QTL was mapped into an interval of RM1347–RM5356 on chromosome 2 using an F2:3 population derived from a cross between XZX45, a cold-sensitive early rice variety from China, and IL43, an introgression line developed by marker-assisted backcrossing. IL43 was created using XN1, a highly cold-resistant cultivar, as the donor parent and XZX45 as the recurrent parent. By integrating transcriptomic data from the target region, we identified Os02g0181300 as the candidate gene for qESCT2. This gene encodes a transcription factor, OsWRKY71. Edited lines of OsWRKY71 exhibited a significantly lower survival rate under cold tolerance compared to the wild type Nipponbare. Further analysis revealed that OsWRKY71 likely regulated cold tolerance at the early seedling stage by a glutathione metabolism related pathway. Additionally, OsWRKY71 exhibits differentiation between indica and japonica subspecies with distinct haplotypes. These findings will facilitate to further research into the genetic basis of cold tolerance at the early seedling stage and enhance the development of cold-resistant rice varieties by marker-assisted selection.